A case report of retained placenta - Mulay, Ameya Sunil; Gupte, Sanjay; Venkataraman, Gayatri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Retained placenta can occur in the setting of significant uterine atony, abnormally adherent placenta, as with placenta accreta spectrum (PAS), or closure of the cervix prior to placental expulsion. Risk factors for retained placenta parallel those for uterine atony and PAS and include prolonged oxytocin use, high parity, preterm delivery, history of uterine surgery, and IVF conceptions.